Assessing age, breeding stage, and mating activity as drivers of variation in the reproductive microbiome of female tree swallows. Issue 16 (29th July 2021) - Hernandez, Jessica; Hucul, Catherine; Reasor, Emily; Smith, Taryn; McGlothlin, Joel W.; Haak, David C.; Belden, Lisa K.; Moore, Ignacio T.
Abstract: Sexually transmitted microbes are hypothesized to influence the evolution of reproductive strategies. Though frequently discussed in this context, our understanding of the reproductive microbiome is quite nascent. Indeed, testing this hypothesis first requires establishing a baseline understanding of the temporal dynamics of the reproductive microbiome and of how individual variation in reproductive behavior and age influence the assembly and maintenance of the reproductive microbiome as a whole. Here, we ask how mating activity, breeding stage, and age influence the reproductive microbiome. We use observational and experimental approaches to explain variation in the cloacal microbiome of free‐living, female tree swallows ( Tachycineta bicolor ). Using microsatellite‐based parentage analyses, we determined the number of sires per brood (a proxy for female mating activity). We experimentally increased female sexual activity by administering exogenous 17ß‐estradiol. Lastly, we used bacterial 16S rRNA amplicon sequencing to characterize the cloacal microbiome. Neither the number of sires per brood nor the increased sexual activity of females significantly influenced female cloacal microbiome richness or community structure. Female age, however, was positively correlated with cloacal microbiome richness and influenced overall community structure. A hypothesis to explain these patterns is that the effect of sexual activity and the number of mates on variation in the cloacal microbiome manifests over an individual's lifetime. Additionally, we found that cloacal microbiome alpha diversity (Shannon Index, Faith's phylogenetic distance) decreased and community structure shifted between breeding stages. This is one of few studies to document within‐individual changes and age‐related differences in the cloacal microbiome across successive breeding stages. More broadly, our results contribute to our understanding of the role that host life history and behavior play in shaping the cloacal microbiomes of wild birds. Abstract : In this paper, we ask the question: how do mating activity, breeding stage, and age influence female reproductive microbiomes? We address this question using observational and experimental approaches to explain both between‐ and within‐individual variation in the cloacal microbiome of free‐living, female birds that exhibit differences in extra‐pair paternity rates. We found that female age and breeding stage, but not number of mates or experimentally elevated sexual activity (via 17ß‐estradiol implants), significantly influenced cloacal microbiome alpha diversity and explained variation in bacterial community structure.